Peer Interaction Does Not Always Improve Children’s Mental State Talk Production in Oral Narratives. A Study in 6- to 10-Year-Old Italian Children - Pinto, Giuliana; Tarchi, Christian; Bigozzi, Lucia (Frontiers in Psychology, 2016)
Joint narratives are a mean through which children develop and practice their Theory of Mind, thus they represent an ideal means to explore children’s use and development of mental state talk. However, creating a learning environment for storytelling based on peer interaction, does not necessarily mean that students will automatically exploit it by engaging in productive collaboration, thus it is important to explore under what conditions peer interaction promotes children’s ToM. This study extends our understanding of social aspects of ToM, focusing on the effect of joint narratives on school-age children’s mental state talk. Fifty-six Italian primary school children participated in the study (19 females and 37 males). Children created a story in two different experimental conditions (individually and with a partner randomly assigned). Each story told by the children, as well as their dialogues were recorded and transcribed. Transcriptions of narratives were coded in terms of text quality and mental state talk, whereas transcriptions of dialogues were coded in terms of quality of interaction. The results from this study confirmed that peer interaction does not always improve children’s mental state talk performances in oral narratives, but certain conditions need to be satisfied. Peer interaction was more effective on mental state talk with lower individual levels and productive interactions, particularly in terms of capacity to regulate the interactions. When children were able to focus on the interaction, as well as the product, they were also exposed to each other’s reasoning behind their viewpoint. This level of intersubjectivity, in turn, allowed them to take more in consideration the contribution of mental states to the narrative.